HUBUNGAN ANTARA PENGALAMAN KORBAN PENYIMPANGAN SEKSUAL EKSIBISIONISME TERHADAP TINGKAT KECEMASAN PADA MAHASISWI FISIP UNIVERSITAS UDAYANA - Chayani Samosir, Zefanya Yuni; Zuryani, Nazrina; Krisna Aditya, I Gusti Ngurah Agung (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
Social deviance is sexual activity that a person undertakes to obtain sexual pleasure in an improper manner. Victims of exhibitionism will usually be frightened, shocked and angry and there are even some victim gets trauma and anxiety. Result on pre-research shown 38 students of Faculty of Social and Political Sciences, Udayana University became victims of exhibitionism. From 40 respondents, discovered there was a significant relationship with the T test and the margin of error is 5%. At low anxiety level is -2,615, the moderate anxiety level is 2,111 and the severe anxiety is 3,935 on student victims of exhibitionism around Udayana University Denpasar Campus. Similarly, results of the F test, it is known that the Fcount is 23,799. The results of this study show that there is a significant relationship between victims of exhibitionism with levels anxiety consisting of low, moderate and severe levels of anxiety. Keywords: Anxiety Level, Exhibitionism, Social Deviance.